Case Report: Surgical Intervention On Drug-influenced Gingival Enlargement Using Diode Laser Therapy - Muhammad Annurdin Sabarudin; Yew Hin Beh; Akram Hassan; Zuryati Abd Ghani (USIM Press, 2024)
Volume: 8 (page: 8-12)